2022
DOI: 10.3390/cancers14153795
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Predictive Outcomes of Recurrent Nasopharyngeal Carcinoma—A Lingering Pitfall of the Long Latency

Abstract: Purpose: To investigate the clinical characteristics, risk factors, and clinical outcomes of long-latent recurrence (>five years) of nasopharyngeal carcinoma (NPC). Methods: This retrospective study enrolled newly diagnosed NPC patients from the Chang Gung Research Database between January 2007 and December 2019. We analyzed the patients’ characteristics and survival outcomes after recurrence. Results: A total of 2599 NPC patients were enrolled. The overall recurrence rate was 20.5%, while 8.1% of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In addition, when the tumor is close to vital organs and structures, the increase in radiation dose may trigger serious or even lethal complications after radiotherapy [ 104 , 105 ]. In order to allow the use of relatively safe and effective re-radiotherapy, some studies have shown that cisplatin, docetaxel, and fluorouracil (TPF) induction therapy is a wise choice [ 106 , 107 ]. However, it has also been suggested that poor compliance with cisplatin in some patients treated with TPF may necessitate new chemotherapy regimens to replace TPF chemotherapy regimens [ 108 , 109 ].…”
Section: Treatment Of Recurrent Npcmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when the tumor is close to vital organs and structures, the increase in radiation dose may trigger serious or even lethal complications after radiotherapy [ 104 , 105 ]. In order to allow the use of relatively safe and effective re-radiotherapy, some studies have shown that cisplatin, docetaxel, and fluorouracil (TPF) induction therapy is a wise choice [ 106 , 107 ]. However, it has also been suggested that poor compliance with cisplatin in some patients treated with TPF may necessitate new chemotherapy regimens to replace TPF chemotherapy regimens [ 108 , 109 ].…”
Section: Treatment Of Recurrent Npcmentioning
confidence: 99%
“…Compared with chemotherapeutic agents, the use of targeted therapy and immunotherapy in recurrent NPC is relatively limited, and in most cases they are not used alone, but in combination with chemotherapeutic agents or radiotherapy to provide better benefits [ 115 , 116 , 117 , 118 , 119 ]. A clinical study published by Ng et al showed that weekly IMRT with docetaxel plus cetuximab was shown to be effective in advanced recurrent NPC compared to TPF-induced chemotherapy, with a 3-year progression-free survival rate of 35.7% [ 107 ]. The results of a multicenter, double-blind phase III clinical trial published in Lancet Oncology in 2021 showed that the GP chemotherapy regimen plus camrelizumab had acceptable toxicity and was effective in prolonging survival in patients with recurrent or metastatic NPC, making it a promising first-line treatment option for patients with recurrent NPC [ 120 ].…”
Section: Treatment Of Recurrent Npcmentioning
confidence: 99%
“…Bone, lung, and liver are common sites of distant metastases, and supraclavicular nodes are the most advanced extent of locoregional spread reported [ 4 ]. A recent retrospective study involving 2,599 NPC patients found that 59% of recurrent NPC occurs within the first two years after completion of treatment [ 5 ]. Axillary lymph node metastasis in NPC is uncommon and rarely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Rapamycin did not induce PGCC formation on its own, nor did it exacerbate PGCC formation brought on by chemotherapy. A recent study established a link between latent PGCCs and the clinical risk of nasopharyngeal carcinoma (NPC) recurrence ( Chen et al., 2022 ). The study demonstrated that mitochondrial changes and chemotherapeutic medications that cause partial mitochondrial damage led to low ATP levels and autophagy activation through the AMPK-mTOR pathway, which in turn helps generate PGCC.…”
Section: Role Of Multinucleated Giant Cells (Mgcs) In Higher Eukaryotesmentioning
confidence: 99%